2019
DOI: 10.1177/1971400919857556
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of apparent diffusion coefficients and enhancement ratios on magnetic resonance imaging in differentiating primary cerebral lymphomas from glioblastoma

Abstract: Background and purpose This study aimed to determine the accuracy of apparent diffusion coefficient (ADC) and enhancement ratio (ER) in discriminating primary cerebral lymphomas (PCL) and glioblastomas. Materials and methods Circular regions of interest were randomly placed centrally within the largest solid-enhancing area of all lymphomas and glioblastomas on both post-contrast T1-weighted images and corresponding ADC maps. Regions of interest were also drawn in the contralateral hemisphere to obtain enhancem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
3
2
Order By: Relevance
“…Although the rT 1 CE of PCNSL was slightly higher than that of GBM, there was no significant difference between the two groups. This result differs from that of the study by Anwar et al ( 9 ), which reported a sensitivity of 83.3%, specificity of 85.7%, and AUC of 0.92 for differentiating PCNSL and GBM. Different study populations, MRI sequence parameters, and timing and dosage of MRI contrast administration may contribute to this inconsistency.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although the rT 1 CE of PCNSL was slightly higher than that of GBM, there was no significant difference between the two groups. This result differs from that of the study by Anwar et al ( 9 ), which reported a sensitivity of 83.3%, specificity of 85.7%, and AUC of 0.92 for differentiating PCNSL and GBM. Different study populations, MRI sequence parameters, and timing and dosage of MRI contrast administration may contribute to this inconsistency.…”
Section: Discussioncontrasting
confidence: 99%
“…Both conventional and advanced MR techniques have been reported to be helpful in differentiating PCNSL from GBM (7)(8)(9)(10)(11)(12). However, most of these studies enrolled all GBM patients, which can be differentiated from PCNSL based on findings of conventional MRI in most cases.…”
Section: Introductionmentioning
confidence: 99%
“…[28] Similarly, Anwar et al report a significant difference in ADC mapping for different tumors. [29] However, data in our study does not demonstrate a significant (P < 0.05) difference between mean ADC of OD Grade II and III. These findings are reflected in literature by Hilario et al and Fellah et al who also found no significant correlation between grade of OD and the mean value of ADC.…”
Section: Tumor Grade and Apparent Diffusion Coefficientcontrasting
confidence: 78%
“…Advanced MRI techniques such as diffusion and texture analysis have been reported to help differentiate primary CNS lymphoma from other neoplasms and inflammatory conditions. 15,16 But there are no reports of their utility in neurolymphomatosis. MRI can also be limited in patients with claustrophobia, implants, pacemaker, or severe renal insufficiency that prevents contrast administration.…”
Section: Discussionmentioning
confidence: 99%